Catalytic activity and stability of encapsulated oxidoreductases for biodegradation of organic pollutants - Nur Atikah Mohidem, 1985-; Hanapi Mat, supervisor; Fakulti Kejuruteraan Kimia (2010)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2010